Comment on “The free aesthetics of Eastern philosophy, the artistic creation and the influence of Eastern philosophy on contemporary visual art” - Fei Tian (Trans/Form/Ação)
Commented article: WU, Z. The free aesthetics of Eastern philosophy, the artistic creation and the influence of Eastern philosophy on contemporary visual art. Trans/Form/Ação: Unesp journal of philosophy, Marília, SP, v. 48, n. 5, p. e025056, 2025. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16978.